Multifold Impact of COVID-19 on Vulnerable Communities in Nepal - Khatiwada, Padma Prasad (Molung Educational Frontier, 2021)
This paper brings out the pressing issue of Corona Virus Disease (COVID-19) pandemic and its multifold impact on the vulnerable communities such as women, children, elderly people, persons with disabilities, and marginalized groups in Nepal. The study identifies the groups corresponding with the kinds of problems and effects in relation to caste/ethnicity, gender, and age. It also categorizes groups in terms of socio-economic conditions such as employment, income, livelihood, access to basic food, shelter, health and education. The analyses based on these issues contribute to highlighting the protection measures for reducing the level of vulnerability. Both the primary and secondary data were collected through desk review and telephonic interviews among the selected women and underprivileged people of the study area. Findings of this study suggest that the pandemic has serious effects that have been seen on vulnerable communities in the area. Curtailment, reduction and/or stop of regular salary or income of the employees from enterprising sectors can have lasting impact on the overall livelihoods of the vulnerable groups unless they are offered special packages to promote their conditions. The research indicates the pandemic as a humanitarian crisis. In such a crisis, only legal treatment and actions may have adverse effects on the poor and helpless people who have lost their resources due to unavoidable situations like lockdown, prohibition order, and insecurity of their jobs.